Penerapan Model Pembelajaran Roar (Read, Observe, Auditory, Review) Berbantukan Media Baamboozle Dalam Meningkatkan Pemahaman Konsep Peserta Didik Pada Mata Pelajaran Ekonomi Kelas XI - Martha Yuniar; Yoni Hermawan; Raden Roro Suci Nurdianti (JOURNAL SAINS STUDENT RESEARCH, 2023)
The main problem related to this research is the low concept understanding ability of students in economic subjects so that the purpose of this study is to determine the effect of using the ROAR (Read, Observe, Auditory, Review) learning model assisted by Baamboozle on students' concept understanding. The method used in this research is an experimental method with a non-equivalent control group design, and data collection techniques through multiple choice tests. The population of this study was all XI social studies classes at SMAN 4 Tasikmalaya in the 2023/2024 school year totaling 186 with 76 samples of students, consisting of 36 experimental class students and 36 control class students with sampling techniques using probability sampling. Data analysis techniques using the help of the SPSS 25 program, namely paired sample t-test and independent sample t-test with a significance level of 5% or 0.05. Based on the results of the study obtained a sig. (2-tailed) value of 0.000 <0.05 which indicates that Ho is rejected so that it can be seen that there is an effect of the ROAR learning model assisted by Baamboozle media on increasing students' concept understanding in economic subjects